2012
DOI: 10.5923/j.materials.20120201.02
|View full text |Cite
|
Sign up to set email alerts
|

Shape Controlled Synthesis of Barium Carbonate Microclusters and Nanocrystallites using Natural Polysachharide – Gum Acacia

Abstract: Different morphosynthesis strategies for BaCO 3 using natural polysaccharide-gum acacia (GA) as templating species are presented. The influence of GA with different functionalities such as -OH, -COOH and -NH 2 on the crystallization and structure formation was investigated. Some interesting morphologies, including rods, dumbbell, double-dumbbell and flower like clusters, can be readily generated by using GA as cooperative modifier in the mineralization process, under the conditions of 0.5%, 1% of templating sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
6
23
0
Order By: Relevance
“…loss) in the temperature range 250e650 C can be attributed due to the decomposition of gum acacia. From our earlier studies it was confirmed by TGA-MS studies, that the evolution of CO 2 during this step is due to the decomposition of eCOOH functional groups present in GA [63]. TGA profiles of HAp synthesized with and without gum acacia (Fig.…”
Section: Tga Studiessupporting
confidence: 70%
“…loss) in the temperature range 250e650 C can be attributed due to the decomposition of gum acacia. From our earlier studies it was confirmed by TGA-MS studies, that the evolution of CO 2 during this step is due to the decomposition of eCOOH functional groups present in GA [63]. TGA profiles of HAp synthesized with and without gum acacia (Fig.…”
Section: Tga Studiessupporting
confidence: 70%
“…This is in agreement with the FT-IR results. It may also be seen that the peak (111) is the strongest in all the BaCO3 crystals synthesized using different adjusters and adjuster concentration, suggesting that BaCO3 crystals are well oriented and grew mainly along the (111) face [12]. In order to further confirm the polymorphs of the as-prepared products in the presence of PA and IPA, the as-prepared products were characterized by FT-IR spectroscopy and the corresponding results are shown in Figure 2 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Spherical BaCO3 crystal can be used for the production of PTC thermistor, which makes capacitors with high dielectric constant and temperature characteristics so that it can exhibit the advantages of small PTC thermistor, high-frequency, highcapacity, and so on [9], which means that different morphologies often have different properties and applications even for the same substance. Therefore, controlled morphology, size and uniform distribution of ultrafine BaCO3powder have attracted more and more research interest [6,[10][11][12]. Control of nucleation, growth, organization of crystals to a superstructure can make their physical properties tunable, which are important for technical application.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the desired elements in the samples would confirm the formation of the respective particles. Elemental analysis of BaSO 4 ( Figure 4a O bond and peak at 1059 cm −1 is attributed to the symmetric C-O stretching vibration [28], thus indicating the formation of BaCO3 particles.…”
Section: Element Analysis Of Ba Salt Particles By Energy Dispersive Xmentioning
confidence: 98%